Pengarusutamaan Moderasi Beragama; Strategi Tantangan dan Peluang FKUB Jawa Timur - Huda, M. Thoriqul (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
Religious moderation is one of the means to strengthen and strengthen a harmonious, safe and peaceful spiritual life. Indonesia is a country with multiple religions, ethnicities, and races, so the adherence to religious moderation in the life of the nation and state is an obligation. The study in this paper is one of the efforts to examine further the East Java Religious Harmony Forum (FKUB) in grounding the attitude of religious moderation in its region. In this study researcher used interviews and observation techniques at the East Java Religious Harmony Forum. The results of this research are that FKUB carries out several strategies to ground religious moderation, including holding discussions on religious moderation, creating a guidebook on religious moderation, strengthening the insight into religious moderation for the millennial generation, and strengthening cooperation with other parties related to religious moderation. Religious moderation program. Furthermore, there are several challenges in grounding religious moderation, including the increasing religious orthodoxy and conservatism, the strengthening of identity politics, and the era of social media. In addition, the culture of the East Java people who are friendly, polite, and tolerant between individuals is one of the strengths and assets for FKUB to continue to ground religious moderation in society.